The Relationship Between Parent's Role with Independence of Children with Mental Retardation During Pandemic - Ngongo, Heni Adrianus; Trishinta, Sirli Mardianna; Hastutiningtyas, Wahidyanti Rahayu (Universitas Airlangga, 2021)
Introduction: The purpose of this study is to determine the relationship of the role of parent with independence of children with mental retardation during the pendemi in SLB N Waibakul District of Central Sumba.Method: The design of the study using the design of the analytic correlation with cross sectional approach. Study population a total of 40 parents who have children with mental retardation in SLB N Waibakul District of Central Sumba and the research sample as many as 40 respondents with the determination using Total Sampling. Techniques of data collection using the instrument in the form of questionnaires, the role of parents and the questionnaire independence of the child with mental retardation. Data analysis methods in use is the Chi Square test.Results: The results of the research prove the majority of 21 (52,5%) respondents gave the role to children with mental retardation during the pendemi the category of less and most of the 22 (55,0%) children with mental retardation experience the independence of the category of dependence currently. The results of the Chi Square test showed a significant relationship, the role of parents with the independence of children with mental retardation during the pendemi in SLB Waibakul District of Central Sumba obtained p value (0,000) < (0,05). Conclusions: The is a significant relationship the role of parents with the independence of children with mental retardation during the pendemi in SLB N Waibakul District of Central Sumba.